Intervention Effect of Long-Term Aerobic Training on Anxiety, Depression, and Sleep Quality of Middle School Students With Depression After COVID-19 - Luo, Lin; Song, Naiqing; Yang, Hao; Huang, JiaHong; Zhou, Ling; Zhang, Liping (Frontiers in Psychiatry, 2021)
Objective: To explore the effects of using RPE exercise intensity monitoring methods and 12-week mid- and low-intensity team aerobic training on anxiety, depression and sleep quality of depressed middle school students after the COVID-19 epidemic. Methods: All study participants were all from a boarding middle school in Chongqing, China. All study participants were screened by the self-rating depression scale and reached the diagnostic criteria for depression. The study subjects were divided into a control group (N = 35) and an exercise group (N = 34). The exercise group performed 30-min night aerobic running four times a week. Use the Borg 6–20 rating of perceived exertion scale (RPE) as a monitoring tool for exercise intensity, and control the exercise intensity at RPE = 11–14. And the control group studied and lived normally. The experiment lasted 12 weeks in total. After the experiment, there were 34 people in the control group and 23 people in the exercise group. The subjects' anxiety, depression and Pittsburgh sleep quality were scored before and after the experiment. Results: After intervention, the depression index (p < 0.01) of the exercise group was significantly lower than that of the control group. Conclusion: Using the RPE exercise intensity monitoring method for 12 weeks of mid- and low-intensity team aerobic training can improve the depressive symptoms of depressed middle school students, and it is beneficial to improve the students' mental health.